Transforming the Transcript to Reflect the Whole Scholar: Legitimizing Pedagogical Training for Graduate Student Instructors - Josh Iorio, PhD; Mark Lowry Decker, MSSW (Park University, 2011)
Although universities acknowledge that teacher training is critical for ensuring quality undergraduate education, research has repeatedly demonstrated that universities typically do an inadequate job of preparing graduate students for their instructor role. In this paper, we show that both graduate students and universities find the pedagogical development of graduate students to be a valid endeavor, and while graduate students strive to legitimize their own pedagogical development, universities must more fully and officially engage in the process. We conclude with a short list of recommendations for universities to consider toward the goal of legitimizing graduate student pedagogical development.